2014
DOI: 10.5455/cap.20130707024051
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Bipolar Disorder

Abstract: ÖzetÖnceleri pediatrik bipolar bozukluk çok nadir görülen bir psikiyatrik bozukluk olarak düşünülse de, son 20 yıldaki araştırmalar bozukluğun sanılandan çok daha yaygın olduğunu ortaya koymuştur. Çocuk ve ergenlik başlangıçlı bipolar bozukluk ciddi ailesel ve akademik sorunlara, daha sık madde kullanımına, riskli cinsel ilişkilere, ergen gebeliği ve suça yatkınlığa neden olmaktadır. Erişkin başlangıçlıya göre yaşam boyu daha kötü bir işlevsellik söz konusudur. Tanı konulması daha güç olabilmekte ve tanı konul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 88 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…It is generally reported that individuals who have pedophilic disorder start to get sexually interested in children during their adolescence; but there are also data indicating that it may be developed at the adulthood (2). As they perform their activities secretly, and do not apply for treatment, it is not possible to determine prevalence of pedophilic disorder (2).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally reported that individuals who have pedophilic disorder start to get sexually interested in children during their adolescence; but there are also data indicating that it may be developed at the adulthood (2). As they perform their activities secretly, and do not apply for treatment, it is not possible to determine prevalence of pedophilic disorder (2).…”
Section: Introductionmentioning
confidence: 99%
“…As they perform their activities secretly, and do not apply for treatment, it is not possible to determine prevalence of pedophilic disorder (2). Majority of pedophilia cases are males (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations